2013
DOI: 10.1002/term.1668
|View full text |Cite
|
Sign up to set email alerts
|

Co-delivery of platelet-derived growth factor (PDGF-BB) and bone morphogenic protein (BMP-2) coated onto heparinized titanium for improving osteoblast function and osteointegration

Abstract: The aim of this study was to improve osteoblast function by delivering two growth factors, PDGF-BB and BMP-2, incorporated onto heparinized titanium (Hep-Ti) substrate. To achieve co-delivery of PDGF-BB and BMP-2, the surface of anodized Ti was immobilized with heparin, and then the two growth factors were coated onto the Hep-Ti surface. Incorporation of the two growth factors onto Hep-Ti was evaluated by SEM and XPS. Incorporated PDGF-BB and BMP-2 were released from the Hep-Ti substrate in a sustained manner.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…ALP activities of cells that are cultured on PDGF-BB and/or BMP/Hepa/Ti were found to be significantly higher than those of cells cultured on untreated Ti on days 7 and 10 (* p < 0.05 and ** p < 0.01). As reported in a previous study [6,56], our finding confirmed that rhBMP-2 and rhPDGF-BB both stimulate osteoblast differentiation. Furthermore, the calcium contents of cells cultured on PDGF-BB or/and BMP/Hepa/Ti were significantly higher than those of cells cultured on untreated Ti on days 7 and 21 (* p < 0.05 and ** p < 0.01).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…ALP activities of cells that are cultured on PDGF-BB and/or BMP/Hepa/Ti were found to be significantly higher than those of cells cultured on untreated Ti on days 7 and 10 (* p < 0.05 and ** p < 0.01). As reported in a previous study [6,56], our finding confirmed that rhBMP-2 and rhPDGF-BB both stimulate osteoblast differentiation. Furthermore, the calcium contents of cells cultured on PDGF-BB or/and BMP/Hepa/Ti were significantly higher than those of cells cultured on untreated Ti on days 7 and 21 (* p < 0.05 and ** p < 0.01).…”
Section: Discussionsupporting
confidence: 91%
“…In the result of previous cell studies [6], PDGF-BB (5 ng/mL)/BMP-2(50 ng/mL)/Hepa/Ti (a 1:10 ratio of growth factors) was significantly higher than BMP/Hepa/Ti, whereas in this study, PDGF-BB (50 ng/mL)/BMP-2 (50 ng/mL)/Hepa/Ti (a 1:1 ratio) was significantly lower than BMP/Hepa/Ti. Furthermore, ALP, calcium deposition, and gene expression not synergistically increased by the copresence of rhPDGF-BB and rhBMP-2.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…47 The ALP activity increased gradually in a time-dependent manner ( Figure 7). Although the ALP activity of the blank nanocomplex group was significantly lower than that of the others, there were no significant differences among the three GF-loaded nanocomplex groups on day 7.…”
mentioning
confidence: 98%